(untitled) (Revista de Ciências Agroveterinárias, 2020)
The air-assisted sprayers produce air stream, which carries the droplets aiding their distribution. However, many droplets are not deposited on the target and are lost to the environment. The use of cabins can reduce operator exposure. Thus, this study aimed to assess the potential dermal and respiratory exposure and the cabin insulation efficiency in pesticide applications in apple orchards. The spray was composed of water plus mancozeb and captan (3.0 L ha-1) and fenitrothion (1.5 L ha-1). The dermal exposure was estimated using absorbent cotton pads fixed in the operator’s protective clothing and inside the cabin. The analytical determination was carried out by Liquid Chromatography with a UV-VIS detector and specific diodes array. The analytes were extracted by ultrasound, as established by the NBR 10004 and described by the United States Environmental Protection Agency. The wavelengths related to the products tested were not detected up to the limit of 200 µg kg-1, indicating that there are good sealing and insulating of the operator inside tested cabins.